1998
DOI: 10.1016/s0735-1097(98)00044-8
|View full text |Cite
|
Sign up to set email alerts
|

Insertion/Deletion Polymorphism of the Angiotensin I-Converting Enzyme Gene Is Associated With Coronary Artery Plaque Calcification As Assessed by Intravascular Ultrasound

Abstract: Patients with CAD and the ACE DD genotype have a significantly higher incidence and greater extent of coronary lesion calcification, as determined by IVUS. This finding indicates that the ACE I/D gene polymorphism is related to the development or progression of atherosclerotic plaque calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 30 publications
0
28
1
Order By: Relevance
“…Pfolhl et al (25) observed a higher incidence and greater extent of coronary lesion calcification, as determined by intravascular ultrasound, in 46 of 146 patients with the DD genotype of the ACE gene. Kardia et al (26) did not find that the apolipoprotein E (apoE) genotypes predicted the presence of CAC in a sample of 329 men and women.…”
Section: Discussionmentioning
confidence: 97%
“…Pfolhl et al (25) observed a higher incidence and greater extent of coronary lesion calcification, as determined by intravascular ultrasound, in 46 of 146 patients with the DD genotype of the ACE gene. Kardia et al (26) did not find that the apolipoprotein E (apoE) genotypes predicted the presence of CAC in a sample of 329 men and women.…”
Section: Discussionmentioning
confidence: 97%
“…Pfohl et al 27 reported an association between the insertion/deletion polymorphism of the angiotensin I-converting enzyme gene and CAC detected by intravascular ultrasound in patients with angiographically documented CAD. Apolipoprotein E genotype was found to influence the relationship between risk factors and EBCT-measured CAC presence in ECAC Study participants.…”
Section: Discussionmentioning
confidence: 99%
“…63 This finding suggested the existence of a possible interaction between cardiovascular risk factors and the ACE polymorphism with respect to carotid IMT. The association between ACE genotype and atherosclerosis was also assessed using coronary calcification as a measure of coronary atherosclerosis, 64,65 and autopsy measurements of aortic atherosclerosis, 66,67 but the results were discordant. In general, a modest positive association between the D allele and atherosclerosis is expected, particularly in those who carry other (genetic or environmental) cardiovascular risk factors.…”
Section: Ace I/d Polymorphism and Atherosclerosismentioning
confidence: 99%